Criminal Acts Of Fraud In Buying And Selling Crypto - Agustinus Christofan; M.Syahrul Borman (Journal of Strafvordering Indonesian, 2025)
The aim of this research is to identify legal loopholes that can be exploited by criminals to commit fraud through cryptocurrency media. This study employs a normative research approach, incorporating a legal perspective. A normative study is a legal research approach that examines doctrinal studies of law. The findings of this research include several case studies and literature that support the argument that cryptocurrency provides opportunities for illegal transactions or other negative activities. Strong speculation suggests that digital currencies are highly vulnerable to being used as a medium for fraud and other abuses, such as financing terrorism, arms and drug trafficking, and various other crimes. This vulnerability arises due to the blockchain-based encryption system of cryptocurrencies, which offers a high level of security, complexity, and anonymity. Furthermore, there are ongoing efforts to establish cryptocurrency as a recognized currency in Indonesia, as evidenced by its increasing use and the emergence of regulations regarding its legality. Therefore, this research highlights the importance of legal oversight in preventing the misuse of cryptocurrency in criminal activities